Studi tentang implementasi komunikasi politik hukum Partai Keadilan Sejahtera (PKS) kabupaten Gowa - Muliaty Amin (State Institute of Islamic Studies (IAIN) Salatiga, 2015)
The main point of this research is that why the implementation of political communication of PartaiKeadilan Sejahtera (PKS) is so important in Gowa regency. The goals of this research are to know PKS’sexistence in extending political communication particularly for people in Gowa regency. The field researchis the method used in this research which is specifically qualitative-naturalistic-inquiry. The approachmethod used is sociology-historic-politic. The source of this research is all managers and membersof Judgement Council Region of PKS in Gowa regency. The method for collecting data is observation,interview, dan documentation. The data validity in this research are done by credibility data checkupwith persistent observation, triangulation, member check, and referential adequacy check. Theoutcome of this research points out that PKS’s existence is displayed by its Perspectives, Missions, andobjectives of PKS establishment. There are three factors influenced to vote or not to vote in NationalElection. At first is a party identity. Secondly is the capability of party in marketing campaign issue. Thelast is a candidate’s performance. The communication ethic that is built by PKS in Gowa regency is thatthe communication ethic together with the internal elite party which is based on basic consideration andstatute of PKS. Meanwhile, PKS’s relation with people and components are established by eithereconomic development or religion experience through Tarbiyah.